Integrating Kolb's Experiential Learning Theory into a sport psychology classroom using a golf-putting activity - Sato, Takahiro; Laughlin, David D. (Journal of sport psychology in action, 2018)
The purpose of this article is to describe the integration of Kolb's Experiential Learning Theory (ELT) within an undergraduate sport psychology course. According to Kolb, experiential learning occurs through a continual process within the four-stage learning cycle: Concrete Experience, Reflective Observation, Abstract Conceptualization, and Active Experimentation. In the course, we used golf-putting tournaments to promote experiential learning during a 15-week semester. Between tournaments, we delivered lectures and facilitated laboratory sessions to discuss and practice sport psychology theories (e.g., Achievement Goal Theory) and skills (e.g., goal-setting, imagery). This article provides a detailed discussion of the structure of golf-putting tournaments, course design, and the use of reflective practice within a sport psychology classroom.